Substance misuse stories among Pacific peoples in New Zealand. (2nd January 2019) - Newcombe, David A. L.; Taufa, Seini; Tanielu, Helen; Nosa, Vili
ABSTRACT: This paper examines the oral stories of Pacific people attending addiction treatment services in Auckland, New Zealand who were participating in a larger study exploring the validity of the Alcohol, Smoking and Substance Involvement Screening Test. (ASSIST). A Talanoa approach was used by interviewers to help gain an understanding of the factors associated with participants' substance misuse. Interviewers made notes of the stories they heard. Fifty participants were interviewed and expressed concerns related to how their substance use was influenced by their peers (66%, n = 33), the environment they were living in (60%, n = 30), and their family (50%, n = 25). Sixteen participants provided detailed narratives of their lived experiences that permitted further in-depth analysis. Thematic analysis of these narratives revealed five interrelated themes; introduction to drugs and alcohol, family dynamics access to drugs, attempts at giving up, and motivation to stop. The use of a Talanoa approach, whilst administering a screening tool, such as the ASSIST, allows for a more in-depth exploration of an individual's substance use. The information gathered would allow those working with Pacific people who misuse alcohol and/or drugs to develop culturally appropriate interventions.